Effect of the Association of Levels of Potassium and Nitrogen from Coated Urea on the Forage Potential of Cactus Pear in Brazilian Savannah Soil - Magalhães, R. M.F.; Edvan, R. L.; Nascimento, K. S. [UNESP]; Nascimento, R. R.; Silva, I. R.; Lacerda, J. J.J.; Morais, E. M.; Lima Neto, A. F.; Araújo, M. J.; Oliveira, M. E. (Taylor & Francis, 2024)
The development of methods that aim to increase the water use efficiency in agricultural systems should be part of the objectives of research, and the cultivation of plants of lower water requirements, such as cactus pear, can be a good option. The purpose of this study was to evaluate the effect of the association of potassium (K) and nitrogen (N) levels from coated urea, in two harvest years, on the agronomic characteristics and nutritive value of Nopalea cochenillifera cv Doce. A randomized block design in a 2 × 4 × 2 factorial arrangement was adopted. The factors corresponded to two levels of K (40 kg and 60 kg ha−1 year−1), four levels of N (0, 60, 120, and 240 kg ha−1 year−1) and two harvest years (Years I and II). The plants were evaluated for growth, yield, chemical, and mineral composition, and nutritive value. The levels of K affected only plant height and K content in the plant. The agronomic variables and contents of ether extract and crude protein (CP) linearly increased along with the levels of N from the coated urea. There was a significant effect of interaction between N levels and harvest year on the contents of NDF, NDFap, NFC, fraction A+B1, Ca, and Mg. The level of 40 kg K ha−1 year−1 associated with 240 kg N ha−1 year−1 from coated urea provided the best results for the characteristics of growth, yield, and nutritive value of the cactus pear.
Keywords: Absorption; efficiency; fertilization; Nopalea cochenillifera; polymers